Hệ thống kiểm soát nội bộ tại Ngân hàng TMCP Đông Á – Chi nhánh Bình Định - Lê Thị Thanh Mỹ (My University, 2014)
Hệ thống kiểm soát nội bộ tại Ngân hàng TMCP Đông Á – Chi nhánh Bình Định
Keywords: Kiểm soát nội bộ; DongA Bank; Bình Định